2001
DOI: 10.1161/hc5001.101749
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Antagonism With Etanercept Improves Systemic Endothelial Vasoreactivity in Patients With Advanced Heart Failure

Abstract: Background — Anti–tumor necrosis factor (TNF)-α therapy with etanercept, a recombinant TNF receptor that binds to and functionally inactivates TNF-α, was shown to improve the functional status of patients with congestive heart failure (CHF). Because administration of TNF-α has been shown experimentally to depress endothelium-dependent relaxation, we hypothesized that TNF-α antagonism with etanercept might improve the depressed systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 25 publications
5
58
0
4
Order By: Relevance
“…In particular, TNF-␣ presumably produced by activated macrophages and vascular endothelial cells has been shown to aggravate the hemodynamics of CHF (14,16). As has been mentioned, clinical studies have demonstrated that targeted anti-TNF-␣ therapy with recombinant TNF-␣ receptor improves the functional status of patients with CHF (18). In this context, the role of ANP in cytokine regulation should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, TNF-␣ presumably produced by activated macrophages and vascular endothelial cells has been shown to aggravate the hemodynamics of CHF (14,16). As has been mentioned, clinical studies have demonstrated that targeted anti-TNF-␣ therapy with recombinant TNF-␣ receptor improves the functional status of patients with CHF (18). In this context, the role of ANP in cytokine regulation should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ in particular has been shown experimentally to depress systemic endothelial vasodilator function and thus aggravates CHF (17). In fact, recent clinical studies have demonstrated that targeted anti-TNF-␣ therapy with etanercept, a recombinant TNF-␣ receptor that binds to and functionally inactivates TNF-␣, improves the functional status of patients with CHF (18). On the other hand, anti-inflammatory cytokines including IL-10 have been speculated to counteract the effects of TNF-␣ (19).…”
mentioning
confidence: 99%
“…On this basis, investigators have argued that the beneficial effects of statins on endothelial function in patients might also be attributable to pleiotropic anti-inflammatory effects (Bonetti et al 2003). More specific interventions, including drugs that bind TNF-α, have also been shown to improve endothelial function in patients with heart failure (Fichtlscherer et al 2001) or rheumatoid arthritis, (Hurlimann et al 2002), and it would be interesting to observe the effects of these or more specific interventions in patients with atherosclerosis.…”
Section: Human Studies Of Systemic Inflammation and Endothelial Dysfumentioning
confidence: 99%
“…Functionally, endothelial inflammatory activation is associated with a profound impairment in endothelium-dependent vasodilator function. [12][13][14] As such, endothelial function may be regarded as an integral index of all inflammatory mediators present in an individual and thus may represent the vascular phenotype of an inflamed patient. Therefore, we tested the hypothesis that assessment of systemic endothelial vasodilator function provides prognostic information in patients suffering from an acute coronary syndrome and is capable of identifying the vulnerable patient who is prone to experience recurrence of instability.…”
mentioning
confidence: 99%